2017
DOI: 10.5194/bg-2017-365
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Algal diversity of temperate biological soil crusts depends on land use intensity and affects phosphorus biogeochemical cycling

Abstract: Biological soil crusts (BSCs) form the most productive microbial biomass in many drylands and disturbed areas with a diverse 10 microalgal community as key component. In temperate regions, BSCs are also common, but generally less studied, and they conduct important ecological functions, like stabilization of soil and enrichment of nutrients. Changes in land use and its intensity strongly influence biodiversity per se and it's role for ecosystem processes, particularly in regions which are densely populated lik… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
3
1
Order By: Relevance
“…This is in contrast with studies carried out in arid or semiarid deserts where cyanobacteria were always dominant in early successional biocrusts [12,31,38,74,75]. However, the presented findings are comparable to other studies conducted in temperate areas [76,77]. In temperate forests, Glaser et al [78] recorded 52 algal species and only very few cyanobacteria in biocrusts.…”
Section: Algae and Cyanobacteriacontrasting
confidence: 87%
See 1 more Smart Citation
“…This is in contrast with studies carried out in arid or semiarid deserts where cyanobacteria were always dominant in early successional biocrusts [12,31,38,74,75]. However, the presented findings are comparable to other studies conducted in temperate areas [76,77]. In temperate forests, Glaser et al [78] recorded 52 algal species and only very few cyanobacteria in biocrusts.…”
Section: Algae and Cyanobacteriacontrasting
confidence: 87%
“…Glaser et al [78] could prove Klebsormidium was the most important biocrust-initiating alga in a temperate forest ecosystem. In an inland dune area in the Netherlands, Pluis [77] found Klebsormidium to be the initial green alga genus in the successional development of the biocrust community. Likewise, representatives of the genus Klebsormidium were found in dynamic dune successional stages along both transects, highlighting the initialization of biocrust development.…”
Section: Algae and Cyanobacteriamentioning
confidence: 99%
“…Several studies have suggested substantial roles of soil crusts in arid regions in phosphorus cycling, particularly in the release of inaccessible organic-P (Crain et al, 2018, Glaser et al, 2017, Baumann et al, 2019. Significant enrichments in the abundance of genes assigned to phosphonate degradation were seen in the soil crust 208 relative to the bulk soil, which were on average 1.04-fold more abundant in the soil crust.…”
Section: Phosphorus Cyclingmentioning
confidence: 99%
“…Microalgae and cyanobacteria are important components of these cryptogamic communities, playing a critical role in nutrient and nitrogen cycling and highly influencing soil oxygen and hydrological regimes. They are active in the top soil layer, forming a thin crust that helps to stabilize soil, maintain its structure, and protect against wind, thermokarst, and water erosions [1][2][3][4][5][6]. In extreme habitats such as alpine and polar ecosystems, where soils are often shallow and exposed, BSCs dominate, providing an important source of nutrition and water for small organisms that would otherwise struggle to survive.…”
Section: Introductionmentioning
confidence: 99%